Propuesta educativa para mejorar la disciplina en el aula, de los estudiantes de décimo año de educación general básica paralelo C de la unidad educativa anexa a la Universidad Nacional de Loja, año lectivo 2013- 2014 - Merino Campoverde, Maria Jael (2016)
Failure to comply with the rules of school life gives way to a series of conflicts within and outside the educational community. This research aims to implement an educational proposal to improve classroom discipline students of tenth year of basic general education. Descriptive study of crosscut and quasi-experimental design; methods used: descriptive, analytic-synthetic, inductive-deductive, historical and logical, comprehensive, scientific diagnostic model and valuation. a survey and Practices Questionnaire J.C. Torrego, applied in a sample of 30 students was used. Results: diagnosis, 66.66% of students do not respect the rules of coexistence, insult in the classroom and fight; the pretest is the 53.33% keep undesirable behaviors in terms of standards of living and 50% inappropriate relationship between partners. After the intervention decreased undesirable behavior in terms of living standards to 26.67% and inadequate relationship between peers to 16.66% (Postest). The r (x, y) is equal to 0.65. It is concluded that the highest percentage of investigated break the rules of coexistence and respect among peers. The educational proposal is valid, it reaches a moderate positive correlation.